Diyanet işleri başkanlığı 4-6 yaş grubu kuran kurslarında kullanılan materyallerin incelenmesi - Yavuz, Hatice Süeda (My University, 2024)
Bu çalışma 2013 yılından itibaren faaliyette olan Diyanet İşleri Başkanlığı 4-6 Yaş Grubu Kur’an Kurslarında kullanılan eğitim materyallerinin 4-6 yaş grubu çocukların gelişim özelliklerine ve okul öncesi materyalinde bulunması gereken özelliklere uygunluğunun incelenmesini ve teorik olarak incelenen bu materyallerin pratikte uygulanış biçimlerinin, verimliliğinin, olumlu ve olumsuz yönlerinin ortaya konmasını amaçlamaktadır. Bunun için öncelikle 4-6 yaş grubu çocukların gelişimleri özellikleri ve öğretim materyalinde bulunması gereken özellikler ele alınmıştır. Bu veriler ışığında 4-6 Yaş Grubu Kur’an Kursları ana materyallerinden Öğretici Kitabı 1-2 ve ek materyallerden Hikâyeler ve Etkinliklerle Değerler Eğitimi Seti incelendikten sonra İstanbul’da görev yapan 15 öğreticiyle mülakat gerçekleştirilmiştir. Araştırma sonucunda materyallerin olumlu ve olumsuz yanları ele alınmış, teorik incelemede uygulanabilir bulunan ancak pratik incelemede uygulanmayan etkinliklerin mevcut olduğu belirlenmiştir. Bu alanda daha önce yapılan akademik çalışmaların incelenmesi sonucunda materyallerin güncellendiği tespit edilmiş ve kurslardaki eğitimin niteliğini artırmak adına bu çalışmada önerilere yer verilmiştir.

This study examines the suitability of teh educational materials used in the Presidency of Religious Affairs 4-6 Age Group Quran Courses, which have been in operation since 2013, with the developmental characteristics of 4-6 age group children and the features that should be included in preschool materials, and the practical application and efficiency of these materials, which are examined theoretically. Aims to reveal its positive and negative aspects. For this purpose, firstly, the developmental characteristics of children aged 4-6 and the features that should be included in the teaching material were discussed. In the light of these data, after examining the Tutorial Book 1-2, one of the main materials of the Quran Courses for 4-6 Ages Group, and the Values Education Set with Stories and Activities, one of the additional materials, interviews were conducted with 15 instructors working in Istanbul. As a result of the research, the positive and negative aspects of the materials were discussed, and it was determined that there were activities that were found applicable in the theoretical examination but not implemented in the practical examination. As a result of the review of previous academic studies in this field, it was determined that the materials were updated and suggestions were included in this study to increase the quality of education in the courses.
Examination of the materials used in the Quran courses of the presidency of religious affairs for the 4-6 age group
Keywords: 4-6 Yaş Grubu Kur’an Kursu; Dini kurumlar; Diyanet İşleri Başkanlığı; Educational Material; Eğitim Materyali Presidency of Religious Affairs; Kur’an kursları; Kur’an-ı Kerim; Öğrenim ve öğretim; Quran Course for 4-6 Age Group; Quran courses; Qurʼan; Religious institutions; Study and teaching; Türkiye